Layered structure for electron beam photoetching process and photoetching process thereof

By introducing a self-crosslinking resin layer between the electron beam photoresist and the substrate, the problem of poor adhesion is solved, the clarity and contrast of the photolithography pattern are improved, and the sensitivity of the electron beam photoresist is significantly improved.

CN119200332AInactive Publication Date: 2024-12-27GUOKE TIANJI (SHANDONG) NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411374330.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Poor adhesion between the electron beam photoresist and the substrate causes the resist pattern to collapse, affecting the quality and contrast of the photolithography pattern.

Method used

A self-crosslinking resin layer is used as the intermediate layer to form a crosslinking polymer by reacting a chain polymer with a crosslinking agent, thereby improving the adhesion between the electron beam photoresist and the substrate, and forming a layered structure.

Benefits of technology

改善了电子束光刻图案的线条清晰度和对比度,显著提高了电子束光刻胶的灵敏度,减少了线条易倒塌现象。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200332A_ABST
    Figure CN119200332A_ABST
Patent Text Reader

Abstract

The invention provides a layered structure for an electron beam lithography process and a lithography process thereof. By adopting the layered structure to carry out electron beam lithography, the problem that electron beam lithography pattern lines are easy to collapse can be effectively improved, the obtained pattern has better line edge roughness, and the pattern lines are clearer. In addition, the obtained photoetching pattern lines also have good contrast. According to the layered structure, the sensitivity of the electron beam photoresist is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, in particular to a layered structure used for electron beam photolithography and a photolithography process thereof. Background Art

[0002] Resolution, contrast and sensitivity are the technical parameters of photoresist. With the development of integrated circuits, the feature size of chip manufacturing is getting smaller and smaller, and the requirements for photoresist are getting higher and higher. The technical parameters of photoresist include resolution, contrast and sensitivity. In order to meet the needs of the development of integrated circuits, photoresist is developing towards high resolution, high contrast and high sensitivity.

[0003] Electron beam photoresist, also known as EB photoresist, refers to photosensitive materials suitable for electron beam exposure technology. Electron beam photoresist must have high contrast, high resolution, high aspect ratio, fast response to electron beam energy, good thermal stability, and good etching resistance. It is widely used in microelectronics manufacturing, semiconductor manufacturing, biomedicine, nanoscience research and other fields.

[0004] In micro-fabrication technology, as the best high-resolution graphics production technology, electron beam lithography has become an important means of precision mask production in integrated circuit technology. Compared with optical lithography, which has always dominated micro-fabrication technology, electron beam lithography has good physical properties. The wavelength of electrons is very short, which makes electron beam lithography have a resolution of nm in theory. In practical applications, a beam spot with a focus size of less than 2nm can be obtained. In addition, electron beam lithography is not limited by the diffraction effect, and has the characteristics of easy focusing and strong controllability. However, during the electron beam lithography process, due to the poor adhesion between the electron beam photoresist and the substrate, the exposed line pattern on the resist collapses, resulting in changes in the resist pattern after development. Summary of the invention

[0005] In order to solve the existing technical defects, the present invention provides a layered structure for electron beam lithography, including upper and lower sides, the upper layer is an electron beam photoresist layer, and the lower layer is a self-crosslinking resin layer. This layered structure can make up for the defect of poor adhesion between the electron beam photoresist and the substrate, thereby improving the quality of the electron beam lithography pattern and enhancing the sensitivity of the electron beam photoresist.

[0006] The technical solution of the present invention is as follows:

[0007] A layered structure for electron beam lithography comprises two layers: the lower layer is a self-crosslinking resin layer, and the upper layer is an electron beam photoresist layer.

[0008] The self-crosslinking resin layer comprises a self-crosslinking resin. The self-crosslinking resin is obtained by reacting a chain polymer with a crosslinking agent. The chain polymer comprises an aromatic group and a nitrogen-containing heterocyclic group. The self-crosslinking resin is a crosslinking polymer.

[0009] According to an embodiment of the present invention, the aromatic group and the nitrogen-containing heterocyclic group are both located on the main chain of the chain polymer.

[0010] According to an embodiment of the present invention, the chain polymer is a polyester-based polymer.

[0011] According to an embodiment of the present invention, the chain polymer is formed by polymerizing at least one compound containing an aromatic group and at least one compound containing a nitrogen-containing heterocycle. For example, the chain polymer is formed by polymerizing a compound containing an aromatic group and two compounds containing nitrogen-containing heterocycles.

[0012] According to an embodiment of the present invention, in the chain polymer, the polymerized units are linked through ester bonds to form the polymer.

[0013] According to an embodiment of the present invention, the aromatic group may be a monocyclic or polycyclic aromatic or heteroaromatic group, for example, C 6-20 Aryl, 5-20 membered heteroaryl; preferably C 6-14 Aryl, 5-14 membered heteroaryl, for example, phenyl, naphthyl, anthracenyl or biphenyl.

[0014] According to an embodiment of the present invention, the compound containing an aromatic group further comprises a carboxyl group, a carboxylate group (such as COOC 1-12 alkyl), a carboxylic anhydride group, or a hydroxyl group.

[0015] According to an embodiment of the present invention, the compound containing an aromatic group further comprises at least two groups selected from carboxylic acid, carboxylic acid ester, carboxylic acid anhydride, and / or at least two hydroxyl groups.

[0016] In some embodiments of the present invention, the compound containing an aromatic group has a structure shown as follows M1':

[0017] ROOC-A-COOR

[0018] M1'

[0019] Wherein, A is selected from the following groups which are unsubstituted or optionally substituted by one, two or more Rs: C 6-20 Aryl, 5-20 membered heteroaryl, C 6-20 Aryl-C 6-20 Aryl or 5-20 membered heteroaryl-5-20 membered heteroaryl; Rs is selected from oxo, halogen, cyano, nitro, C 1-12 Alkyl, C1-12 Alkoxy, C 3-12 Cycloalkyl or 3-12 membered heterocyclic group;

[0020] R is selected from C 1-12 alkyl.

[0021] In some embodiments of the present invention, in M1', A is selected from C 6-14 Aryl, 5-14 membered heteroaryl, C 6-14 Aryl-C 6-14 Aryl or 5-14 membered heteroaryl-5-14 membered heteroaryl;

[0022] R is selected from H, C 1-6 alkyl.

[0023] In some specific embodiments of the present invention, the compound containing an aromatic group is, for example, the following compound:

[0024]

[0025] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocyclic ring further comprises a carboxyl group, a carboxylate group (such as COOC 1-12 alkyl), a carboxylic anhydride group, or a hydroxyl group.

[0026] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocycle further comprises at least two groups selected from carboxylic acids, carboxylic acid esters, carboxylic acid anhydrides, and / or at least two hydroxyl groups.

[0027] According to an embodiment of the present invention, the compound containing a nitrogen-containing heterocycle is a compound of the following general formula I:

[0028]

[0029] Wherein, R1 and R2 are the same or different and are selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5; R3 is selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5, R6;

[0030] R4, R5, R6 are the same or different and are selected from H, optionally replaced by one or more R a Substituted with the following groups: C 1-12 Alkyl, C 2-12 Alkenyl, C 2-12 Alkynyl, aryl, heteroaryl;

[0031] R aare the same or different and are selected from oxo, halogen, cyano, nitro, alkyl, cycloalkyl, heterocyclyl, aryl, heteroaryl, -NR b R c 、-OR d 、-CO-R d 、-COOR d 、-SR e 、-SO-R e 、-SO2-R e ;

[0032] R b , R c same or different, independently selected from hydrogen or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl;

[0033] R d , R e The same or different, independently selected from H, or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl, 3-12 membered heterocyclic group.

[0034] In some specific embodiments of the present invention, the compound containing a nitrogen-containing heterocycle includes the compounds shown in the following M2' and M3':

[0035]

[0036] Among them, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-12 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 Alkyl; R 33 Selected from H, C 1-12 Alkyl, aryl, heteroaryl, -C 1-12 Alkyl-OH, -C 1-12 Alkyl-OC 1-12 Alkyl, -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 alkyl.

[0037] In some embodiments of the present invention, R 21, R 22 , R 23 The same or different, independently selected from -C 1-6 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 Alkyl; R 33 Selected from H, C 1-6 Alkyl, -C 1-6 Alkyl-OH, -C 1-6 Alkyl-OC 1-6 Alkyl, -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 alkyl.

[0038] In some specific embodiments of the present invention, the compound containing a nitrogen-containing heterocyclic ring is, for example, tris(2-hydroxyethyl)isocyanurate and tris(2-carboxyethyl)isocyanurate.

[0039] In some embodiments of the present invention, the chain polymer is a polymer obtained by reacting M1', M2' and M3'.

[0040] Furthermore, when R 31 , R 32 , R 33 All three groups are -C 1-12 When alkyl-COOH is used, C 1-12 The fatty alcohol caps the unreacted COOH in monomer M3'.

[0041] The crosslinking agent of the present invention can be a crosslinkable compound having at least two substituents capable of forming crosslinks. The crosslinking agent can be an amino crosslinking agent. For example, a glycoluril-based crosslinking agent, a melamine-based crosslinking agent, a urea-based crosslinking agent, a benzoguanamine-based crosslinking agent, or a phenolic compound having a substituent capable of forming crosslinks such as methylol and methoxymethyl.

[0042] In some embodiments of the present invention, the crosslinking agent may be, for example, methoxymethylated glycoluril or methoxymethylated melamine, such as tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril or hexamethoxymethyl melamine. The crosslinking agent may be commercially available. For example, glycoluril-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 1170, 1171 and 1172; melamine-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 300, 301, 303, 350, 370, 380, 1116 and 1130; urea-based crosslinking agents sold by American Cyanamide Company under the trade names of Powderlink 1174, 1196, Beetle 60, 65 and 80; and benzoguanamine-based crosslinking agents sold by American Cyanamide Company under the trade names of Cymel 1123 and 1125.

[0043] In some embodiments of the present invention, the cross-linking agent has a structure as shown in the following formula IC:

[0044]

[0045] Wherein, s is an integer from 1 to 12;

[0046] R7 and R8 are the same or different and are independently selected from H, C 1-12 Alkyl, C 6-14 Aryl or 5-14 membered heteroaryl;

[0047] R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-12 alkyl.

[0048] According to an embodiment of the present invention, s is an integer of 1-6, such as 1, 2, 3, 4;

[0049] According to an embodiment of the present invention, R7 and R8 are the same or different and are independently selected from H, C 1-6 Alkyl, phenyl; for example, H, methyl, ethyl, propyl, butyl or phenyl.

[0050] According to an embodiment of the present invention, R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-6 The alkyl group is, for example, methyl, ethyl, n-propyl or n-butyl.

[0051] In some specific embodiments of the present invention, the cross-linking agent is selected from the following structures:

[0052]

[0053] According to an embodiment of the present invention, the weight average molecular weight of the self-crosslinking resin is 1000-8000, such as 2000-7000, 3000-6000 or 4000-5000.

[0054] According to an embodiment of the present invention, the molecular weight distribution coefficient of the self-crosslinking resin is less than 2.5, such as 1.10-1.25, 1.25-1.50, 1.50-2.00, 2.00-2.04, 2.04-2.08 or 2.08-2.14.

[0055] In some specific embodiments of the present invention, the self-crosslinking resin has the structural units shown below:

[0056]

[0057]

[0058] According to an embodiment of the present invention, the electron beam resist layer includes an electron beam resist resin, and the electron beam resist resin is, for example, a copolymer of an aromatic vinyl monomer and an α-halogenated acrylate monomer.

[0059] According to an embodiment of the present invention, the aromatic vinyl monomer is selected from at least one of α-methylstyrene monomer and 4-fluoro-α-methylstyrene monomer.

[0060] According to an embodiment of the present invention, the α-haloacrylate monomer is selected from at least one of α-methyl chloroacrylate monomer, α-ethyl chloroacrylate monomer, α-benzyl chloroacrylate monomer, α-chloroacrylate-1-adamantyl ester monomer, α-chloroacrylate-2,2,3,3,3-pentafluoropropyl monomer, α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer, α-fluoroacrylate methyl monomer, α-fluoroacrylate ethyl monomer, α-fluoroacrylate benzyl ester monomer, α-fluoroacrylate-1-adamantyl ester monomer, α-fluoroacrylate-2,2,3,3,3-pentafluoropropyl monomer and α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer.

[0061] In some specific embodiments of the present invention, the electron beam photoresist resin is a copolymer of α-methylstyrene and 2-methylchloroacrylate:

[0062]

[0063] According to an embodiment of the present invention, the weight average molecular weight of the electron beam photoresist resin is 20,000-100,000, such as 20,000-50,000, 50,000-56,300, 56,300-58,000, 58,000-68,300, 68,300-69,900, 69,900-75,000 or 75,000-100,000.

[0064] According to an embodiment of the present invention, the molecular weight distribution coefficient of the electron beam photoresist resin is less than 2.5, such as 1.10-1.25, 1.25-1.50, 1.50-2.00, 2.00-2.04, 2.04-2.08 or 2.08-2.14.

[0065] According to an embodiment of the present invention, the electron beam photoresist layer is prepared from an electron beam photoresist composition.

[0066] According to an embodiment of the present invention, the electron beam photoresist composition comprises the electron beam photoresist resin as described above and a solvent. The solvent is, for example, selected from at least one of anisole, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, gamma-butyrolactone and ethyl lactate, preferably anisole.

[0067] According to an embodiment of the present invention, the electron beam photoresist composition may further include an auxiliary agent, wherein the auxiliary agent is selected from at least one of a surfactant, a photoacid generator, a viscosity controller, and a stabilizer.

[0068] According to an embodiment of the present invention, the surfactant includes: a nonionic surfactant, for example, polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether; polyoxyethylene polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate and sorbitan tristearate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate fluorinated surfactants. For example, EF301, EF303, EF352, F171, F173, R-30, R-40, R-30-N, FC430, FC431, AG7 10, S-382, SC101, SC102 and silicone polymer KP341.

[0069] According to an embodiment of the present invention, the surfactant may be mixed in the photoresist composition as a single species or as a plurality of species.

[0070] According to an embodiment of the present invention, the photoacid generator is selected from at least one of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, (4,8-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4,7-dihydroxy-1-naphthyl)dimethylsulfonium trifluoromethanesulfonate, (4-methoxynaphthyl)diphenylsulfonium trifluoromethanesulfonate, (4-phenylthiophenyl)diphenylsulfonium trifluoromethanesulfonate, 2-(benzo[d][1,3]dioxolan-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxyphenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-[4-(4-methoxyphenyl)phenyl]-4,6-bis(trichloromethyl)-1,3,5-triazine.

[0071] According to an embodiment of the present invention, the viscosity control agent is selected from at least one of butanol, chloroform, ethanol, water, acetonitrile, hexane and isopropanol.

[0072] According to an embodiment of the present invention, the stabilizer is at least one selected from p-benzoquinone, methylhydroquinone, p-hydroxyanisole, 2-tert-butylhydroquinone and 2,5-di-tert-butylhydroquinone.

[0073] In some specific embodiments of the present invention, the electron beam photoresist composition comprises: an electron beam photoresist resin, a surfactant and a solvent.

[0074] According to an embodiment of the present invention, the mass ratio of the electron beam photoresist resin solution, the surfactant and the solvent is 1:(0.0001-0.1):(8-30), for example, 1:(0.008-0.08):(10-25) or 1:(0.001-0.05):(12-20);

[0075] Wherein, the electron beam photoresist resin solution is a solution with a solid content of 5 to 20% of the electron beam photoresist resin.

[0076] In some specific embodiments of the present invention, the electron beam photoresist composition comprises: electron beam photoresist resin, R-40 and anisole.

[0077] According to an embodiment of the present invention, the self-crosslinking resin layer is prepared from a self-crosslinking resin composition.

[0078] According to an embodiment of the present invention, the self-crosslinking resin composition comprises the self-crosslinking resin as described above and a solvent, the solvent being, for example, methyl 2-hydroxyisobutyrate:

[0079] In some embodiments of the present invention, the thickness of the self-crosslinking resin layer is, for example, 5-100 nm, such as 10-40 nm.

[0080] In some embodiments of the present invention, the thickness of the electron beam photoresist layer is, for example, 5-100 nm, such as 10-40 nm.

[0081] In some embodiments of the present invention, the thickness of the self-crosslinking resin layer is less than the thickness of the electron beam photoresist layer.

[0082] According to an embodiment of the present invention, the layered structure further comprises a substrate, and the substrate is connected to the self-crosslinking resin layer, that is, a three-layer structure is formed from bottom to top: substrate, self-crosslinking resin layer, electron beam photoresist layer.

[0083] According to the present invention, the substrate is, for example, silicon, silicon dioxide, silicon carbide, ceramic, quartz, etc.

[0084] The present invention also provides a method for preparing the above-mentioned layered structure, comprising: first coating a self-crosslinking resin composition on a substrate to form a self-crosslinking resin layer; and then coating an electron beam photoresist composition on the self-crosslinking resin layer to form an electron beam photoresist layer.

[0085] In some embodiments of the present invention, the self-crosslinking resin composition is coated on the substrate by a method such as spin coating, and baked at a certain temperature to obtain a self-crosslinking resin layer; and then the electron beam photoresist composition is coated on the self-crosslinking resin layer by a method such as spin coating, and baked at a certain temperature to obtain an electron beam photoresist layer. The baking temperature is, for example, 160 to 250° C., such as 160 to 170° C., 170 to 180° C., 180 to 190° C., or 190 to 200° C. The baking time is, for example, 60 to 300 seconds, such as 120 to 180 seconds or 180 to 240 seconds.

[0086] In some embodiments of the present invention, the self-crosslinking resin composition is coated on the substrate by spin coating and then baked at 160-250° C. for 50-250 seconds.

[0087] In some embodiments of the present invention, the electron beam photoresist composition is coated on the self-crosslinking resin layer by spin coating and then baked at 160-190° C. for 100-250 seconds.

[0088] The present invention also provides a method for forming a photolithography pattern, comprising: subjecting the layered structure of the present invention to electron beam exposure, post-baking, development and fixing.

[0089] According to an embodiment of the present invention, the layered structure of the present invention is exposed in an electron beam lithography machine, for example, the electron beam lithography voltage is 100KV, the current is 100pA; the exposure energy range is set to 75-425μC / cm2 , for example 150~175μC / cm 2 .

[0090] In some embodiments of the present invention, the post-baking temperature is, for example, 60 to 100° C. The post-baking time is, for example, 60 to 240 seconds.

[0091] In some embodiments of the present invention, the developer used in the development is, for example, at least one of butyl acetate, methyl isobutyl ketone, n-hexane, cyclohexanone, amyl acetate, and isopropanol, for example, amyl acetate or a mixture of amyl acetate and isopropanol, and the developing time is, for example, 30 to 240 seconds.

[0092] In some embodiments of the present invention, the fixing solution used in the fixing is, for example, isopropyl alcohol, and the fixing time is, for example, 5 to 60 seconds.

[0093] Beneficial Effects

[0094] The present invention provides a layered structure, wherein a self-crosslinking resin layer is added between an electron beam photoresist layer and a substrate, wherein the self-crosslinking resin has a polar group in its structure, and thus adhesion can be improved. The layered structure of the present invention is used for electron beam lithography, and the problem that the lines of the electron beam lithography pattern are prone to collapse can be effectively improved, and the obtained pattern has a good line edge roughness, and the pattern lines are clearer. In addition, the obtained lithography pattern lines also have a good contrast. The layered structure of the present invention significantly improves the sensitivity of the electron beam photoresist. BRIEF DESCRIPTION OF THE DRAWINGS

[0095] Figure 1 The exposure dose is 150μC / cm 2 The following are scanning electron microscope images of the photolithography process of Examples 1-3 (a: Example 1; b: Example 2; c: Example 3).

[0096] Figure 2 The exposure dose is 175μC / cm 2 The following scanning electron microscope images of the photolithography process of Examples 4-6 (a: Example 4; b: Example 5; c: Example 6)

[0097] Figure 3 It is a schematic diagram of the operation of the photolithography process of the present invention. DETAILED DESCRIPTION

[0098] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0099] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0100] Synthesis Example 1

[0101]

[0102] Synthesis steps of the self-crosslinking resin DT used for the bottom coating: 9g of dimethyl 2,6-naphthalene dicarboxylate (M1), 13.0g of tris(2-hydroxyethyl) isocyanurate (M2), 8.6g of tris(2-carboxyethyl) isocyanurate (M3), 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole are added to the reaction flask in no particular order. The reaction flask is heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction is complete, the anisole and n-butanol in the reaction flask are distilled off. Subsequently, the resulting reactant is diluted with 67.8g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.09 g of methyl-2-hydroxyisobutyrate and 10.9 g of 1,3,4,6-tetrakis(methoxymethyl)glycoluril (C1) were added to the obtained 19.2 g polymer solution, stirred at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered, and dried to obtain 16 g (M 2 ) of polymer DT resin solid powder. W =3514, M W / Mn=1.888).

[0103] Synthesis Example 2

[0104] Preparation method of electron beam polymer resin: 891.60g (4.0mol) of α-methylstyrene monomer and 606.00g (5.2mol) of methyl 2-chloroacrylate monomer are dissolved in 400g of anisole. After the temperature in the reactor is stabilized at 35+ / -1°C, the monomer solution is added to the reactor. After the monomer solution is added, the external temperature is set to 40°C. After the temperature of the solution in the reactor rises to 40+ / -1°C, the initiator solution (anisole solution containing 1.29g of azobisisobutyronitrile) is added to the reactor, and the container is washed twice with 25g of anisole, and the washing solution is added to the reactor. After the initiator solution is added, the external temperature is set to 60°C. Heat to 85°C. Then add a dioxane solution containing 0.50g of azobisisobutyronitrile, continue to react for 24 hours, cool to room temperature, and finally precipitate, wash, and dry the reaction solution to obtain 400g of electron beam polymer resin solid powder. GPC test data: weight average molecular weight 58687, molecular weight distribution 1.91.

[0105] Resin solution EBP: Weigh 23 g of the above-mentioned solid powder and 180 g of anisole, add them into a 500 mL brown glass bottle in turn, and place them in a shaker for 1 hour to fully dissolve; after the dissolution is completed, the mixed solution is circulated and filtered with a 40 nm Nuc filter for 24 hours to finally obtain a resin solution EBP with a solid content of 11.06%.

[0106] Synthesis Example 3

[0107]

[0108]

[0109] The synthesis steps of the self-crosslinking resin DT-2 (TJ-2) used for the bottom coating are as follows: 9g of dimethyl 2,6-naphthalene dicarboxylate, 13.0g of tris(2-hydroxyethyl) isocyanurate, 8.6g of tris(2-carboxyethyl) isocyanurate, 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole are added to the reaction flask in no particular order. The reaction flask is heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction is complete, the anisole and n-butanol in the reaction flask are distilled off. Subsequently, the obtained reactant is diluted with 66.8g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.19g of methyl-2-hydroxyisobutyrate and 9.92g of crosslinker C2 are added to the obtained 20.2g polymer solution, stirred for reaction at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered and dried to obtain 16 g (M) of polymer TJ-2 resin solid powder. W =4375,M W / Mn=2.010).

[0110] Synthesis Example 4

[0111]

[0112]

[0113] The synthesis steps of the self-crosslinking resin DT-3 (TJ-3) used for the bottom coating are as follows: 9g of dimethyl 2,6-naphthalene dicarboxylate, 13.0g of tris(2-hydroxyethyl) isocyanurate, 8.6g of tris(2-carboxyethyl) isocyanurate, 0.24g of p-toluenesulfonic acid monohydrate, 5.16g of n-butanol and 14.6g of anisole are added to the reaction flask in no particular order. The reaction flask is heated to 140-160°C and stirred vigorously for 6 hours to react. After the reaction is complete, the anisole and n-butanol in the reaction flask are distilled off. Subsequently, the obtained reactant is diluted with 68.2g of methyl 2-hydroxyisobutyrate and neutralized with triethylamine. 4.31g of methyl-2-hydroxyisobutyrate and 12.89g of crosslinker C3 are added to the obtained 18.3g polymer solution, stirred for reaction at 50°C for 3 hours, cooled to room temperature, and neutralized with triethylamine. The obtained reactant was then precipitated, and the obtained precipitate was washed, filtered and dried to obtain 14 g (M) of polymer TJ-3 resin solid powder. W =3345, M W / Mn=1.740).

[0114] The components of the coating solutions for forming the bottom coating layer and the upper electron beam photoresist in the photolithography process of Examples 1-6 are shown in Table 1 below.

[0115] Table 1

[0116]

[0117] In the above table, “ / ” means that the component is not contained.

[0118] The surfactant in the above table is R-40.

[0119] The composition of the bottom coating and the upper electron beam photoresist in the photolithography process of the following Examples 1-6 and the test effect data are shown in Table 2 below.

[0120] Table 2

[0121]

[0122] In Table 2, the “-” in the lower layer column indicates that there is no lower layer. The “-” in the line width column indicates that the photolithography pattern is too poor and the specific line width cannot be tested.

[0123] Example 1

[0124] No self-crosslinking bottom coating was applied, only a 50nm thick electron beam photoresist layer was applied. After shaking the sample T50 prepared according to Table 1 above for 12 hours, it was filtered with a 0.22 micron polyethylene microporous filter to obtain a clarified filtrate. The prepared electron beam photoresist solution was used as follows: spin-coated the above electron beam photoresist solution on a 2-inch silicon wafer, the spin coating speed was 3000rpm, and the coating thickness of the electron beam photoresist was 50nm; pre-baked at 180°C for 180s; exposed in an electron beam lithography machine, the electron beam lithography voltage was 100KV, the current was 100pA, and the exposure energy range was set to 150μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, and fix with isopropyl alcohol for 10 seconds. The pattern morphology is observed by scanning electron microscopy. Figure 1 a, at an exposure energy of 150μC / cm 2 Although the contrast is good, no obvious line pattern can be observed and the lithography result is not feasible.

[0125] Example 2

[0126] First, spin-coat a 10nm thick self-crosslinking bottom coating, and then apply a 40nm thick electron beam photoresist. Shake the samples T40 and R10 prepared according to Table 1 above for 12 hours, and then filter them with 0.22 micron polyethylene microporous filters to obtain clear filtrates. Spin-coat the two prepared solutions as follows: spin-coat the bottom coating R10 on a 2-inch silicon wafer at a spin-coating speed of 1500rpm, and pre-bake at 215°C for 60s; the coating thickness is 10nm; then spin-coat the electron beam photoresist T40 on the bottom coating at a spin-coating speed of 3000rpm, pre-bake at 180°C for 180s, and the coating thickness of the electron beam photoresist is 40nm; expose in an electron beam lithography machine, the electron beam lithography voltage is 100KV, the current is 100pA, and the exposure energy range is set to 150μC / cm 2 ; then post-baked at 90°C for 2 min; developed in developer, the developer was amyl acetate, the developing time was 60 s, and fixed with isopropanol for 10 s. The pattern morphology was observed by scanning electron microscopy. Figure 1 b, at an exposure energy of 150μC / cm 2 When using the RGB mode, clear line graphics can be observed with good contrast.

[0127] Example 3

[0128] First, spin-coat a 20nm thick self-crosslinking bottom coating, and then apply a 30nm thick electron beam photoresist. Shake the samples T30 and R20 prepared according to Table 1 above for 12 hours, and then filter them with 0.22 micron polyethylene microporous filters to obtain clarified filtrates. Spin-coat the two prepared solutions as follows: spin-coat the bottom coating R20 on a 2-inch silicon wafer at a spin speed of 1500rpm, and pre-bake at 215°C for 60s; the coating thickness is 20nm; then spin-coat the electron beam photoresist T30 on the bottom coating at a spin speed of 3000rpm, pre-bake at 180°C for 180s, and the coating thickness of the electron beam photoresist is 30nm; expose in an electron beam lithography machine, the electron beam lithography voltage is 100KV, the current is 100pA, and the exposure energy range is set to 150μC / cm 2 ; then post-baked at 90°C for 2 min; developed in developer, the developer was amyl acetate, the developing time was 60 s, and fixed with isopropanol for 10 s. The pattern morphology was observed by scanning electron microscopy. Figure 1 c, at an exposure energy of 150μC / cm 2 When using the RGB mode, clear line graphics can be observed with good contrast.

[0129] Example 4

[0130] No self-crosslinking bottom coating was applied, only a 50nm thick electron beam photoresist layer was applied. After shaking the sample T50 prepared according to Table 1 above for 12 hours, it was filtered with a 0.22 micron polyethylene microporous filter to obtain a clarified filtrate. The prepared electron beam photoresist solution was used as follows: spin-coated the above electron beam photoresist solution on a 2-inch silicon wafer, the spin coating speed was 3000rpm, and the coating thickness of the electron beam photoresist was 50nm; pre-baked at 180°C for 180s; exposed in an electron beam lithography machine, the electron beam lithography voltage was 100KV, the current was 100pA, and the exposure energy was 175μC / cm 2 ; then post-bake at 90°C for 2 minutes; develop in developer, the developer is amyl acetate, the development time is 60 seconds, and fix with isopropyl alcohol for 10 seconds. The pattern morphology is observed by scanning electron microscopy. Figure 2 a, at an exposure energy of 175μC / cm 2 Although the contrast is good, no obvious line patterns can be observed.

[0131] Example 5

[0132] First, spin-coat a 10nm thick self-crosslinking bottom coating, and then apply a 40nm thick electron beam photoresist. Shake the samples T40 and R10 prepared according to Table 1 above for 12 hours, and then filter them with 0.22 micron polyethylene microporous filters to obtain clarified filtrates. Spin-coat the two prepared solutions as follows: spin-coat the bottom coating R10 on a 2-inch silicon wafer at a spin speed of 1500rpm, and pre-bake at 215°C for 60s; the coating thickness is 10nm; then spin-coat the electron beam photoresist T40 on the bottom coating at a spin speed of 3000rpm, pre-bake at 180°C for 180s, and the coating thickness of the electron beam photoresist is 40nm; expose in an electron beam lithography machine, the electron beam lithography voltage is 100KV, the current is 100pA, and the exposure energy range is set to 175μC / cm 2 ; then post-baked at 90°C for 2 min; developed in developer, the developer was amyl acetate, the developing time was 60 s, and fixed with isopropanol for 10 s. The pattern morphology was observed by scanning electron microscopy. Figure 2 b, at an exposure energy of 175 μC / cm 2 When using the RGB mode, clear line graphics can be observed with good contrast.

[0133] Example 6

[0134] First, spin-coat a 20nm thick self-crosslinking bottom coating, and then apply a 30nm thick electron beam photoresist. Shake the samples T30 and R20 prepared according to Table 1 above for 12 hours, and then filter them with 0.22 micron polyethylene microporous filters to obtain clarified filtrates. Spin-coat the two prepared solutions as follows: spin-coat the bottom coating R20 on a 2-inch silicon wafer at a spin speed of 1500rpm, and pre-bake at 215°C for 60s; the coating thickness is 20nm; then spin-coat the electron beam photoresist T30 on the bottom coating at a spin speed of 3000rpm, pre-bake at 180°C for 180s, and the coating thickness of the electron beam photoresist is 30nm; expose in an electron beam lithography machine, the electron beam lithography voltage is 100KV, the current is 100pA, and the exposure energy range is set to 175μC / cm 2 ; then post-baked at 90°C for 2 min; developed in developer, the developer was amyl acetate, the developing time was 60 s, and fixed with isopropanol for 10 s. The pattern morphology was observed by scanning electron microscopy. Figure 2 c, at an exposure energy of 175 μC / cm 2 When using the RGB mode, clear line graphics can be observed with good contrast.

[0135] Comparing the lithography results of Examples 2 and 3 with Example 1 and Examples 5 and 6 with Example 4, it is found that when the overall thickness is 50 nm and the dense line / groove pattern with a period of 100 nm is designed, the resin polymer of the self-crosslinking reaction system is applied as a bottom coating on the silicon wafer, and then the electron beam photoresist is spin-coated. It is observed by scanning electron microscopy that the exposure energy is 150 and 175 μC / cm 2 The obtained pattern lines are clearer and the contrast is also very good. Therefore, the problem of easy collapse of the electron beam lithography pattern lines can be effectively improved by using the layered structure of the present invention for electron beam lithography, and the obtained pattern has good line edge roughness and the pattern lines are clearer. In addition, the obtained photolithography pattern lines also have a good contrast. The layered structure of the present invention significantly improves the sensitivity of the electron beam photoresist.

[0136] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A layered structure for electron beam lithography, characterized in that It consists of two layers: The lower layer is a self-crosslinking resin layer, and the upper layer is an electron beam photoresist layer.

2. The layered structure according to claim 1, characterized in that The self-crosslinking resin layer includes a self-crosslinking resin. Preferably, the self-crosslinking resin is obtained by reacting a chain polymer with a crosslinking agent. Preferably, the chain polymer includes an aromatic group and a nitrogen-containing heterocyclic group. Preferably, the aromatic group and the nitrogen-containing heterocyclic group are both located on the main chain of the chain polymer. Preferably, the chain polymer is a polyester based polymer. Preferably, the chain polymer is formed by polymerizing at least one compound containing an aromatic group and at least one compound containing a nitrogen-containing heterocyclic ring. Preferably, in the chain polymer, the polymer units are linked via ester bonds to form the polymer. Preferably, the aromatic group may be a monocyclic or polycyclic aromatic or heteroaromatic group, for example, C 6-20 Aryl, 5-20 membered heteroaryl; preferably C 6-14 Aryl, 5-14 membered heteroaryl, for example, phenyl, naphthyl, anthracenyl or biphenyl. Preferably, the compound containing an aromatic group further comprises a carboxyl group, a carboxylate group, a carboxylic acid anhydride group, or a hydroxyl group. Preferably, the compound containing an aromatic group further comprises at least two groups selected from carboxylic acid, carboxylic acid ester, carboxylic acid anhydride, and / or at least two hydroxyl groups. Preferably, the compound containing a nitrogen-containing heterocyclic ring further comprises a carboxyl group, a carboxylate group, a carboxylic acid anhydride group, or a hydroxyl group. Preferably, the compound containing a nitrogen-containing heterocycle further comprises at least two groups selected from carboxylic acids, carboxylates, carboxylic anhydrides, and / or at least two hydroxyl groups.

3. The layered structure according to claim 1 or 2, characterized in that The compound containing an aromatic group has a structure shown in the following M1': ROOC-A-COOR M1’ Wherein, A is selected from the following groups which are unsubstituted or optionally substituted by one, two or more Rs: C 6-20 Aryl, 5-20 membered heteroaryl, C 6-20 Aryl-C 6-20 Aryl or 5-20 membered heteroaryl-5-20 membered heteroaryl; Rs is selected from oxo, halogen, cyano, nitro, C 1-12 Alkyl, C 1-12 Alkoxy, C 3-12 Cycloalkyl or 3-12 membered heterocyclic group; R is selected from C 1-12 alkyl. Preferably, in M1', A is selected from C 6-14 Aryl, 5-14 membered heteroaryl, C 6-14 Aryl-C 6-14 Aryl or 5-14 membered heteroaryl-5-14 membered heteroaryl; R is selected from H, C 1-6 alkyl. Preferably, the compound containing an aromatic group is the following compound: Preferably, the compound containing a nitrogen-containing heterocycle is a compound of the following general formula I: Wherein, R1 and R2 are the same or different and are selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5; R3 is selected from -C 1-12 Alkyl-OR4, -C 1-12 Alkyl-COOR5, -C 1-12 Alkyl-OCOR5, R6; R4, R5, R6 are the same or different and are selected from H, optionally replaced by one or more R a Substituted with the following groups: C 1-12 Alkyl, C 2-12 Alkenyl, C 2-12 Alkynyl, aryl, heteroaryl; R a are the same or different and are selected from oxo, halogen, cyano, nitro, alkyl, cycloalkyl, heterocyclyl, aryl, heteroaryl, -NR b R c 、-OR d 、-CO-R d 、-COOR d 、-SR e 、-SO-R e 、-SO2-R e ; R b , R c same or different, independently selected from hydrogen or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl; R d , R e The same or different, independently selected from H, or optionally replaced by one, two or more R a Substituted with the following groups: C 1-12 Alkyl, C 3-12 Cycloalkyl, 3-12 membered heterocyclic group. Preferably, the compound containing a nitrogen-containing heterocycle includes the compounds represented by the following M2' and M3': Among them, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-12 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 Alkyl; R 33 Selected from H, C 1-12 Alkyl, aryl, heteroaryl, -C 1-12 Alkyl-OH, -C 1-12 Alkyl-OC 1-12 Alkyl, -C 1-12 Alkyl-COOH or -C 1-12 Alkyl-COOC 1-12 alkyl. Preferably, R 21 , R 22 , R 23 The same or different, independently selected from -C 1-6 Alkyl-OH; R 31 , R 32 The same or different, independently selected from -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 Alkyl; R 33 Selected from H, C 1-6 Alkyl, -C 1-6 Alkyl-OH, -C 1-6 Alkyl-OC 1-6 Alkyl, -C 1-6 Alkyl-COOH or -C 1-6 Alkyl-COOC 1-6 alkyl. Preferably, the compound containing a nitrogen-containing heterocyclic ring is, for example, tris(2-hydroxyethyl)isocyanurate and tris(2-carboxyethyl)isocyanurate. Preferably, the chain polymer is a polymer obtained by reacting M1', M2' and M3'.

4. The layered structure according to any one of claims 1 to 3, characterized in that The crosslinking agent is a crosslinkable compound having at least two substituents capable of forming crosslinks. Preferably, the crosslinking agent is an amino crosslinking agent, such as a glycoluril crosslinking agent, a melamine crosslinking agent, a urea crosslinking agent, a benzoguanamine crosslinking agent, or a phenolic compound having a substituent capable of forming a crosslink, such as hydroxymethyl and methoxymethyl. Preferably, the crosslinking agent is methoxymethylated glycoluril or methoxymethylated melamine, such as tetramethoxymethyl glycoluril, tetrabutoxymethyl glycoluril or hexamethoxymethyl melamine.

5. The layered structure according to any one of claims 1 to 4, characterized in that The cross-linking agent has a structure shown in the following formula IC: Wherein, s is an integer from 1 to 12; R7 and R8 are the same or different and are independently selected from H, C 1-12 Alkyl, C 6-14 Aryl or 5-14 membered heteroaryl; R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-12 alkyl. Preferably, s is an integer from 1 to 6; Preferably, R7 and R8 are the same or different and are independently selected from H, C 1-6 Alkyl, phenyl; for example, H, methyl, ethyl, propyl, butyl or phenyl. Preferably, R9, R 10 , R 11 , R 12 The same or different, independently selected from C 1-6 The alkyl group is, for example, methyl, ethyl, n-propyl or n-butyl. Preferably, the cross-linking agent is selected from the following structures: Preferably, the weight average molecular weight of the self-crosslinking resin is 1000-8000. Preferably, the molecular weight distribution coefficient of the self-crosslinking resin is less than 2.

5. Preferably, the self-crosslinking resin has the structural units shown below:

6. The layered structure according to any one of claims 1 to 5, characterized in that The electron beam photoresist layer includes an electron beam photoresist resin, and the electron beam photoresist resin is, for example, a copolymer of an aromatic vinyl monomer and an α-halogenated acrylate monomer. Preferably, the aromatic vinyl monomer is selected from at least one of α-methylstyrene monomer and 4-fluoro-α-methylstyrene monomer. Preferably, the α-halogenated acrylate monomer is selected from at least one of α-methyl chloroacrylate monomer, α-ethyl chloroacrylate monomer, α-benzyl chloroacrylate monomer, α-chloroacrylate-1-adamantyl ester monomer, α-chloroacrylate-2,2,3,3,3-pentafluoropropyl monomer, α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer, α-fluoroacrylate methyl monomer, α-fluoroacrylate ethyl monomer, α-fluoroacrylate benzyl ester monomer, α-fluoroacrylate-1-adamantyl ester monomer, α-fluoroacrylate-2,2,3,3,3-pentafluoropropyl monomer and α-chloroacrylate-2,2,3,3,4,4,4-heptafluorobutyl monomer. Preferably, the electron beam photoresist resin is a copolymer of α-methylstyrene and 2-methylchloroacrylate:

7. The layered structure according to any one of claims 1 to 6, characterized in that The electron beam photoresist layer is prepared from an electron beam photoresist composition. Preferably, the electron beam photoresist composition comprises the electron beam photoresist resin as described above and a solvent. The solvent is, for example, selected from at least one of anisole, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, propylene glycol monoacetate, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol methyl ethyl ether, butyl acetate, neopentyl acetate, γ-butyrolactone and ethyl lactate. Preferably, the electron beam photoresist composition may further include an auxiliary agent, wherein the auxiliary agent is selected from at least one of a surfactant, a photoacid generator, a viscosity controller, and a stabilizer. Preferably, the electron beam photoresist composition comprises: electron beam photoresist resin, R-40 and anisole. Preferably, the self-crosslinking resin layer is prepared from a self-crosslinking resin composition. Preferably, the self-crosslinking resin composition comprises the self-crosslinking resin as described above and a solvent.

8. The layered structure according to any one of claims 1 to 7, characterized in that The thickness of the self-crosslinking resin layer is 5-100 nm. Preferably, the thickness of the electron beam photoresist layer is 5-100 nm. Preferably, the layered structure further comprises a substrate, and the substrate is connected to the self-crosslinking resin layer.

9. A method for preparing the layered structure according to any one of claims 1 to 8, characterized in that: include: Firstly, a self-crosslinking resin composition is coated on a substrate to form a self-crosslinking resin layer; Then, an electron beam photoresist composition is coated on the self-crosslinking resin layer to form an electron beam photoresist layer.

10. A method for forming a photolithographic pattern, characterized in that: include: The layered structure according to any one of claims 1 to 8 is subjected to electron beam exposure, post-baking, development and fixing.

Citation Information

Patent Citations

  • Method for producing polymer compound and polymer compound

    CN104487484A

  • Organic bottom antireflective coating composition for nanolithography

    CN105505146A

  • Coating composition for forming resist underlayer film for EUV lithography process

    CN111116357A

  • Method for removing metal ion impurity in polymer compound for photolithography

    JP2010189563A